Prescribing trends of statins in Scotland: A drug utilization study (Bangladesh Journal of Pharmacology, 2013)
Statins are highly effective in managing hypercholesterolaemia in patients with or without chronic heart disease due to extensive evidence for safety, efficacy and cost effectiveness. Observational cross sectional retrospective cohort study was done in approximately 200 primary care practices in Scotland. Frequency, rates and time trends for statin prescriptions together with demographic data and the prescribing patterns for high dose simvastatin and newer statins in its place was measured. 63%, 27%, 5%, 4% and 1% patients were prescribed simvastatin, atorvastatin, pravastatin, rosuvastatin and fluvastatin respectively (n=1,91370). Prevalence for individual statin as well as for all statin prescriptions, significantly increased (p